Mainstreaming the Ambition, Coherence, and Comprehensiveness of the Post-2020 Global Biodiversity Framework Into Conservation Policy - Carroll, Carlos; Rohlf, Daniel J.; Epstein, Yaffa (Frontiers in Conservation Science, 2022)
Parties to the Convention on Biological Diversity are finalizing a new Global Biodiversity Framework (GBF) to more effectively guide efforts by the world’s nations to address global loss of biodiversity and ecosystem services. Each party is required to mainstream these new targets into national conservation strategies. To date, such strategies have been criticized as largely aspirational and lacking clear linkages to national policy mechanisms, which has contributed to the world’s general failure to meet the Convention’s previous targets. We use the United States and European Union as examples to compare and contrast opportunities and barriers for mainstreaming the GBF more effectively into policy. The European Union and United States have unique relationships to the Convention, the former being the only supranational party and the latter, having signed but never ratified the treaty, adopting Convention targets on an ad hoc basis. The contrasting conservation policy frameworks of these two polities illustrate several conceptual issues central to biodiversity conservation and demonstrate how insights from the GBF can strengthen biodiversity policy even in atypical contexts. We focus on three characteristics of the GBF which are essential if policy is to effectively motivate and guide efforts to halt biodiversity loss: comprehensiveness, coherence, and ambition. Statutes in both the United States and European Union provide a strong foundation for mainstreaming the GBF’s comprehensiveness, coherence, and ambition, but policy development and implementation falls short. We identify six common themes among the reforms needed to successfully achieve targets for reversing biodiversity loss: broadening conservation focus to all levels of biodiversity, better coordinating conservation strategies that protect sites and landscapes with those focused on biodiversity elements (e.g., species), coordinating biodiversity conservation with efforts to safeguard ecosystem services including ecosystem-based climate mitigation and adaptation, more coherent scaling of targets from global to local extents, adoption of a more ambitious vision for recovery of biodiversity, and development of effective tracking and accountability mechanisms.